Behavioural Analysis of Handover Mechanism in Heterogeneous Wi-Li-Fi Environment - Sivananaintha peruma, P; Arunmozhi Selvi, S; Joel, John K; Rajesh, RS (International Journal of Computer Sciences and Engineering, 2025)
Light-fidelity (Li-Fi) is a dominant technology for wireless networking working on the principle of visible light communication (VLC). Li-Fi has wide-bandwidth, licence-free characteristics enables communication in radio frequency (RF) sensitive environments, realizes energy-efficient data transmission, and has the potential to boost the capacity of wireless access network through divergence. The new network environment called hybrid Wi-Li-Fi system developed, utilizing unidirectional Li-Fi channel as downlink and Wi-Fi channel as both uplink and downlink. The handover in traditional heterogeneous RF based wireless network has already been analyzing. However integration of Li-Fi network with heterogeneous RF network will create a hybrid Het-Net and the handover method also become highly conjugate. In this paper, we analysed hybrid heterogeneous handover schemes while user equipment (UE) rotate and roam and novel insights are analysed. Experimental results revealed that the hybrid system out performs the conventional Wi-Fi, and Li-Fi environment for the crowded environments in terms of throughput, delay time and handover rate.